Integrating Critical Qur’anic Discourse In A Pesantren-Based University: A Study of ISQI Sunan Pandanaran, Yogyakarta - Abdul Kadir; Muhammad Alwi HS; Ni’mah Afifah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This study aims to critically examine how Orientalist discourse is integrated into the formal curriculum of pesantren-based Islamic higher education institutions in Indonesia, with a specific focus on ISQI Sunan Pandanaran Yogyakarta. The main argument of this research is that Islamic universities—even those rooted in pesantren tradition—are capable of facilitating a productive encounter between faith and critical rationality within the academic sphere. Using a qualitative approach and data collection techniques such as classroom observation and interviews with the head of the Qur’anic Studies program and 54 ISQI students, the study finds that Orientalist materials actually encourage a recontextualization of Qur’anic studies that balances faith with critical reasoning. Student reception indicates growth in reflective, argumentative skills and openness to interdisciplinary approaches. The findings suggest that pesantren have significant potential to become spaces for global epistemic dialogue when supported by inclusive and reflective pedagogical structures. The study recommends further exploration of cross-discursive curricular dynamics in contemporary Islamic education.